If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 8(-6) = -24 Multiply 8 * -6 4x + -48 = -24 Reorder the terms: -48 + 4x = -24 Solving -48 + 4x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + 4x = -24 + 48 Combine like terms: -48 + 48 = 0 0 + 4x = -24 + 48 4x = -24 + 48 Combine like terms: -24 + 48 = 24 4x = 24 Divide each side by '4'. x = 6 Simplifying x = 6
| 10x+40-3x=98-9x-26 | | 64-9x^2=0 | | r^2-4r+3=0 | | 345-x=7 | | 8x-7+x=9x-3-4x | | 0=0 | | -4.9t+10t+2=8 | | p^2+8p+7=0 | | 21x^2+57x-108=0 | | -.5(x+6)=.5(x+8) | | 30-3x=6x+18 | | (y+1)(y+1)=0 | | 5x-(2x-1)=16 | | 66x=5280*1.446 | | 3x^2-9x=27 | | 12-7x=126-28x | | 9x+6+14x=x+5+24x | | 16w^2-1=0 | | 2p^2+10p+8=0 | | 4x+38=12x-26 | | 0.3=-20z | | 3n^2+11n-4=0 | | v^2+6v-16=0 | | 9(x-6)=4(x-1) | | -8x^3-452x^2-224x=0 | | 12y^2+21y-6=0 | | y-7.7=0.3 | | 14x+15y=16 | | 3n^3-12n^2=0 | | 0.2n+n=4.8 | | 3-5x=-47 | | 3y+8=3y-2y |